Bilateral morphea en coup de sabre: a rare presentation of linear morphea - Hania Qamar Khan; Mohammad Adil; Syed Suhail Amin; Mohd Mohtashim; Roopal Bansal; Fatima Tuz Zahra (Termedia Publishing House, 2021)
Morphea en coup de sabre is a type of linear localized scleroderma, characterized by a sclerotic skin band in the forehaead and frontoparietal scalp area. It can cause cicatricial alopecia, when affecting the scalp. The disease is mostly unilateral and may be associated with neurological complications and eye defects. Herein, we present a case of bilateral morphea en coup de sabre in a young man, which developed following trauma to the head in childhood 10 years earlier. It produced linear bands of alopecia over the scalp and right eyebrow. The lesions progressed over 4 years, then remained quiescent for 6 years and then restarted progressing again. The patient also complained of repeated frontal headaches but the neurological and ocular examination was normal. Dermoscopy and histopathology were used to confirm the diagnosis. The case is unique because of the bilateral manifestation, preceding trauma and recurrence of disease activity.